Prevalence of eating disorder risk and its associated factors among high school adolescents in Terengganu, Malaysia - Nizatul Nurain, M.; Nurulhuda, M.H. (2019)
Eating disorder is most commonly occur among adolescents due to weight concern and body dissatisfaction. Screening for eating disorders based on early identification of an eating disorder risk factor can lead to early treatment, thereby reducing serious complication and psychological complications. This study aimed to determine the prevalence of eating disorder risk and its associated factors among high school adolescents. A cross-sectional survey was conducted among 620 school-adolescents aged between 14 and 18 years from 11 secondary schools in Terengganu. Cluster sampling was applied and a self-administered questionnaire was used to assess 4 main components of the study: Eating Disorder Risk, Sociodemographic Factors, Substance Misuse Index and Psychological Factor. Eating Attitude Test (EAT-26) is used to assess risk of eating disorder as it has 3 subscales to assess an individual’s behaviours, thoughts on dieting, bulimia and food preoccupation and oral control. Substance Misuse Index drug is divided into 2 main categories licit and illicit drugs. Psychological factors was measured using validated Malay version of strength and difficulties questionnaires (SDQ). Prevalence of eating disorder risk among schoolgoing adolescents were 32.3%. The prevalence of eating disordered risk was higher among girls (18.4%) as compared to boys (13.9%). It was independently associated with emotional problem (p=0.028, Adjusted OR 1.15, CI 1.02, 1.30) and peer problem (p=0.004, Adjusted OR 1.23, CI 1.07, 1.42) identified using SDQ after adjusting other variables. Increasing age also increased the risk for eating disorder (p=0.014, Adjusted OR 1.20, CI 1.04, 1.38). It was not significantly associated with body mass index (BMI), or any history of any form of previous abuse. Adolescents with emotional and peer problems are at risk for eating disordered. It is crucial to screen adolescents identified with these problems for eating disorders in order to evade or reduce the potential harmful complications associated with it.